Penyuluhan Masyarakat: Penerapan Prinsip-Prinsip Dasar Pengelolaan Perusahaan dalam Perspektif Hukum untuk Meningkatkan Akuntabilitas Panti Asuhan Claresta - Rolib Sitorus; Joy Zaman Felix Saragih; Muhammad Daffa Syahputra; Sheila Ananda Siregar; Ananda Bima Al Wajdi Majid Pranoto (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Community Service (PkM) aims to provide education and capacity building to foster children at the orphanage regarding the basic principles of company management. As a for-profit institution, rather than a non-profit social institution, its management requires a systematic managerial approach to run effectively, efficiently, and sustainably. Through this (PkM), it is hoped that they will be able to understand basic concepts such as planning, organizing, leadership, and control as part of good governance practices. The method of implementation of the activity is counseling or interactive lectures involving all children and the orphanage administrators. The material is delivered verbally and visually using presentation media, accompanied by question and answer sessions and case studies to make it more applicable and easy to understand. A participatory approach is used so that participants are active in discussions and can relate the material to real situations at the orphanage. The results of the activity show an increase in the knowledge of foster children and orphanage administrators regarding the basic concepts of company management, particularly regarding the importance of activity planning, division of roles and tasks, and transparent financial records. Participants stated that this activity provided new insights that can be directly applied in the day-to-day management of the orphanage. This activity also builds awareness that the application of managerial principles is not only relevant for business companies, but also for social institutions in achieving their humanitarian goals in a sustainable manner.